Chinatown [videorecording (DVD)] - Polanski, Roman; Nicholson, Jack; Dunaway, Faye; Huston, John, 1906-1987 (Paramount, 2017)
A seemingly routine matrimonial snooping job mushrooms into a murderous scandal in pre-World War II Los Angeles.